How to promote effective irrigation pricing reform in northern China? Insights from the Taocheng District. Issue 4 (3rd July 2020) - Chen, Sicheng; Wang, Yahua; Svensson, Jesper
ABSTRACT: There has been a growing interest in understanding the enabling conditions for the adoption of irrigation pricing reform worldwide. We enrich the literature on policy diffusion by comparing the effects of different mobilization patterns in northern China, showing how differences in incentives have hampered or fostered the spread of a collect-and-refund policy in Taocheng District. We find that the mobilization pattern of water authorities, with limited fiscal resources and weak political influence, provided little incentive for local authorities to adopt the policy. By contrast, the mobilization pattern of government chiefs mobilized local authorities to spread the policy across larger scales.